Modulation of angiotensin II-induced vasoconstriction by endothelium-derived relaxing factor in the isolated microperfused rabbit afferent arteriole. - Ito, S (1991)
Although endothelium-derived relaxing factor (EDRF) has been studied extensively in large vessels, little is known about its role in the preglomerular afferent arteriole (Af-Art). We tested the hypothesis that EDRF, which is produced locally in the Af-Art, modulates arteriolar responses to angiotensin II (AII). A single rabbit Af-Art with its glomerulus intact was microperfused in vitro at 60 mmHg. When 0.1 microM AII was first applied, luminal diameter decreased by 49 +/- 7.0% (n = 9; P less than 0.0001); however, constriction waned, with the decrease becoming 15 +/- 3.5% at 1 min. After washing the Af-Art, repeated AII caused less constriction (13 +/- 4.0%; P less than 0.0002 vs. first application), showing tachyphylaxis. Pretreatment with Nw-nitro-L-arginine (N-Arg), which inhibits synthesis of nitric oxide (an EDRF), decreased basal diameter by 18 +/- 3.0% (n = 14; P less than 0.0001). N-Arg also augmented AII-induced constriction (86 +/- 6.8%; P less than 0.02 vs. nontreated Af-Art) and rendered it persistent (82 +/- 6.9% at 1 min). Even after pretreatment with N-Arg, repeated AII caused a weaker response, which was restored by washing with kidney homogenate rich in angiotensinase. In conclusion, this study provides evidence that local production of EDRF is an important determinant of the tone of the Af-Art. Our results suggest that the transient nature of AII-induced constriction of the Af-Art may be due to production of EDRF, while tachyphylaxis may be the result of long lasting receptor occupancy.